ANALISIS KASUS PENCURIAN YANG DILAKUKAN OLEH ANAK BERDASARKAN ASAS RESTORATIF - Riska Andini Hasnabila; Tundjung Herning Sitabuana (Fakultas Hukum Universitas Tarumanagara, 2021)
This is an analysis of Court Conclusion Number 9/PID. SUS-ANAK/2016/PT.BDG, which examines whether the appellate court judge's ruling, which is based on the restorative justice concept, is appropriate. The research uses an analytical descriptive method with a normative juridical strategy to explain and investigate the elements that judges consider while making judgments. Because the judge evaluates the case based on restorative justice ideals, the appeal court judge's decision confirming the decision of the first-level court judges is the proper choice. The judge examines not only the attempt to have a deterrent impact, but also the best interests of children who are in trouble with the law, as well as the best interests of children who are not in dispute with the law.such as ensuring that children's educational rights are met and that they are not exposed to harmful influences that may lead to a return of crime. Education, health care, and advocacy for all children, regardless of origin, race, gender, disability, or ability, should be considered in the problem of children in confrontation with the law. The children are unable to acquire a decent education due to the prison's incapacity to provide proper education to its inmate